Diversity and Inclusion in Advertising: Beyond the Buzzwords: Diversity and Inclusion in Advertising: Beyond the Buzzwords - Sjukun, Sjukun (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study investigates the impact of advertising representation and inclusion policies on consumer trust and brand perception at PT. XYZ Medan, a biscuit manufacturing company. Using quantitative methods and employing SmartPLS for data analysis, the research finds significant direct effects of Representation in Ads and Inclusion Policies on both Consumer Trust and Brand Perception. Furthermore, the study reveals significant indirect effects, highlighting the mediating role of Consumer Trust in the relationship between Representation in Ads / Inclusion Policies and Brand Perception. The findings underscore the importance of authentic representation and comprehensive inclusion policies in fostering consumer trust and enhancing brand perception. These insights are crucial for companies aiming to strengthen their market position through inclusive marketing strategies that resonate with diverse consumer groups.